Analisis Kualitas Pelayanan Tenaga Kependidikan Kepada Mahasiswa di Fakultas Ilmu Sosial Universitas Puangrimaggalatung - Risda Handayani; Erna Erna; Eka Patmasari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the quality of services provided by education staff to students at the Faculty of Social Sciences, Puangrimaggalatung University by using a qualitative approach, through in-depth interviews and observations, this study explores students' views, experiences, and perceptions of various aspects of services provided by education staff, which include reliability, responsiveness, assurance, empathy, and physical evidence of Student Needs. The data obtained were analyzed with thematic analysis techniques to identify patterns and themes related to service quality. The results of this study show that although the majority of students are satisfied with the services received, there are several challenges that need to be considered, such as when they want to take the signature in question, and the attitude of empathy towards students is not even. This research provides important insights for the faculty to improve the quality of education staff services in order to better meet the needs and expectations of students, thereby creating a better academic experience.